See how the land lies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Evolving Land Rights, Policy and Tenure in Africa Edited by C Toulmin & J Quan. IIED and DFID, 2000. 324 pp. ISBN 1899825517 GBP 12.50 Euro 19.60 (free to non-OECD)